Application of wide selected‐ion monitoring data‐independent acquisition to identify tomato fruit proteins regulated by the CUTIN DEFICIENT2 transcription factor. Issue 15 (10th May 2016) - Martin, Laetitia B. B.; Sherwood, Robert W.; Nicklay, Joshua J.; Yang, Yong; Muratore‐Schroeder, Tara L.; Anderson, Elizabeth T.; Thannhauser, Theodore W.; Rose, Jocelyn K. C.; Zhang, Sheng
Abstract : We describe here the use of label‐free wide selected‐ion monitoring data‐independent acquisition (WiSIM‐DIA) to identify proteins that are involved in the formation of tomato ( Solanum lycopersicum ) fruit cuticles and that are regulated by the transcription factor CUTIN DEFICIENT2 (CD2). A spectral library consisting of 11 753 unique peptides, corresponding to 2338 tomato protein groups, was used and the DIA analysis was performed at the MS1 level utilizing narrow mass windows for extraction with Skyline 2.6 software. We identified a total of 1140 proteins, 67 of which had expression levels that differed significantly between the cd2 tomato mutant and the wild‐type cultivar M82. Differentially expressed proteins including a key protein involved in cutin biosynthesis, were selected for validation by target SRM/MRM and by Western blot analysis. In addition to confirming a role for CD2 in regulating cuticle formation, the results also revealed that CD2 influences pathways associated with cell wall biology, anthocyanin biosynthesis, plant development, and responses to stress, which complements findings of earlier RNA‐Seq experiments. Our results provide new insights into molecular processes and aspects of fruit biology associated with CD2 function, and demonstrate that the WiSIM‐DIA is an effective quantitative approach for global protein identifications.